Pengembangan Bahan Ajar Digital Berbantuan Canva Siswa Kelas IV UPT SDN 064034 Medan - Silvia, Silvia; Muhammad Noer Fadlan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to develop Canva-assisted digital teaching materials using the Discovery Learning model for Civic Education (PKn) on the topic